Revisitando o desenvolvimento brasileiro : o BNDE e o financiamento de longo prazo - 1952/1964 - Araújo, Victor Leonardo Figueiredo Carvalho de (2010)
This thesis aims to discuss the origins of the Brazilian National Bank of Economic Development (BNDE). Specifically, this thesis analyzes the BNDE s financial format: the bank, since its creation, in 1952, obtain its resources from fiscal funds, without demand it to the monetary authority (the Bank of Brasil) like did others development banks around the world. The central hypothesis is that such financial format was compatible with the two main economics schools during that period: the Monetarists who believed that the economic development had to be financed without monetary emissions because it could create inflation and the Development Tradition that believed that the fiscal funds creation was a way to provide resources to the economic development without forced savings.